Ta’lîm al-Lughah al-‘Arabiyyah al-Badawiyyah li Tat?awwur al-Taqaddum ‘al al-Daulah al-Umawiyyah; al-Dirâsah al-Tah?lîliyyah Hîlâl al-Manhaj wa al-T?arîqah - Bashirotul Hidayah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2016)
A Bedouin Arab tribes until the now famous eloquent, beautiful Arabic language and literature, believed the Umayyad Caliphs to teach Arabic in young people by sending them to their home villages later appeared term badawî, which is a special place to teach Arabic being taught directly by the Bedouin. From the statement, researchers interested in analyzing the lives of Bedouin Arabs who still lumpy his Arabization (culture of the Arabs in the fushâ Arabic language and cultural). How curriculum is learning Arabic that is used by the Bedouins? And how Arabic language teaching methodology used by the Bedouins? This type of research is a library research, note at that time in the Bedouin community is not familiar with the term curriculum and methodology in education, only from the various references i have found and writers associated with the current education there are some similarities. So the authors concluded several curriculum used by the Bedouin community in the teaching of Arabic fushâ is al-ta’wîd (habituation), bî’ah lughawiyah (language environment), and advice. While the methodology is in the form of al-rih?lah (travel search teachers), al-istimâ’ (hearing), al-kalâm (oral communication), and al-kitâbah (write science that has been studied).